Estimating the lactate threshold using wireless near-infrared spectroscopy and threshold detection analyses - Cayot, T. E.; Robinson, S. G.; Davis, L. E.; Bender, P. A.; Thistlethwaite, J. R.; Broeder, C. E.; Lauver, J. D. (International Journal of Exercise Science, 2021)
The present investigation examined the ability of two threshold detection analyses (maximum distance, Dmax; modified maximum distance, mDmax) in identifying the near-infrared spectroscopy (NIRS) threshold, a lactate threshold (LT) estimate, from exercising tissue oxygen saturation (StO2) responses. Additionally, the test-retest reliability of exercising StO2 and total hemoglobin concentration (THC) responses were examined at moderate and peak cycling intensities. Fourteen healthy, recreationally active participants performed maximal incremental step cycling tests (+25 W / 3 minutes) to volitional fatigue on two separate occasions while StO2 and THC of the vastus lateralis were monitored. Exercising blood [lactate] was collected during Session One. LT and NIRS thresholds (NIRS1, NIRS2) were then determined using Dmax and mDmax threshold analyses. Significant (p < 0.05), moderate correlations were detected between LT and NIRS1 when using Dmax (LT = 130 ± 49 W, NIRS1 = 136 ± 34 W, r = 0.690), but not for mDmax (r = 0.487). No significant test-retest reliability for the NIRS thresholds were observed for Dmax (ICC = 0.351) or mDmax (ICC = 0.385). Exercising StO2 responses demonstrated good reliability (ICC = 0.841-0.873) while exercising THC responses demonstrated moderate-good reliability (ICC = 0.720-0.873) at moderate and peak exercise intensities. The results of this study suggest that neither the Dmax nor mDmax threshold analyses should be used to estimate the LT due to the unreliable detection of the NIRS threshold from session to session.